Assessment of walkability and walkable routes of a 15-min city for heat adaptation: Development of a dynamic attenuation model of heat stress - Wang, Yu; He, Bao-Jie; Kang, Chong; Yan, Li; Chen, Xueke; Yin, Mingqiang; Liu, Xiao; Zhou, Tiejun (Frontiers in Public Health, 2022)
Actively addressing urban heat challenges is an urgent task for numerous cities. Existing studies have primarily developed heat mitigation strategies and analyzed their cooling performance, while the adaptation strategies are far from comprehensive to protect citizens from heat-related illnesses and deaths. To address this research gap, this paper aims to enhance people's adaptation capacity by investigating walkability within fifteen-minute cities (FMC). Taking cognizance of thermal comfort, health, and safety, this paper developed a dynamic attenuation model (DAM) of heat stress, along with heat stress aggravation, continuance, and alleviation. An indicator of remaining tolerant heat discomfort (Rt) was proposed with the integration of the Universal Thermal Climate Index (UTCI) to assess heat-related walkability. Following an empirical study among 128 residents in Mianyang, China, and assessing four levels of heat stress, the maximum tolerant heat discomfort was determined to be 60 min. Furthermore, the DAM was applied to an FMC with 12 neighborhoods in Fucheng, Mianyang, China. The results indicate that for each neighborhood, the street was generally walkable with an Rt ranging between 15 and 30 min, after walking for 900 m. A population-based FMC walkability was further determined, finding that the core area of the FMC was favorable for walking with an Rtof 45–46 min, and the perpetual areas were also walkable with an Rtof 15–30 min. Based on these results, suggestions on the frequency of public services (frequently used, often used, and occasionally used) planning were presented. Overall, this paper provides a theoretical model for analyzing walkability and outlines meaningful implications for planning heat adaptation in resilient, safe, comfortable, and livable FMCs.